Perlindungan Hukum Fungsi Lingkungan terhadap Penebangan Pohon di Sidoarjo - Prasetyo, Andika Bujang; Phahlevy, Rifqi Ridlo (Wadah Inovasi Indonesia, 2023)
The article discusses the protection of environmental functions, especially trees in Sidoarjo government policies carried out by the Sidoarjo Environmental Service against business actors. Aiming at the people of Sidoarjo can get a good living environment and fulfillment of human rights. The research method is conducted normative juridical by means of norm analysis and norm interpretation, with a statutory approach (statue approach), and using descriptive analysis. The results of this study indicate that the protection of the environmental function of trees in Sidoarjo district has not maximally protected the protection of the function of the tree itself. Based on the interview process and the findings of the academic paper, which has a lot of updates from Regent Regulation Number 29 of 2018 concerning Trees on the Edge of the Road, in the content of the Academic Paper.